High‐Resolution Aircraft Observations of Turbulence and Waves in the Free Atmosphere and Comparison With Global Model Predictions. Issue 16 (23rd August 2022) - Dörnbrack, Andreas; Bechtold, Peter; Schumann, Ulrich
Abstract: High‐resolution flight data obtained from in situ measurements in the free atmosphere aboard the High Altitude and Long Range Research Aircraft (HALO) are used to determine eddy dissipation rates along extended flights during the recent Southern Hemisphere Transport, Dynamics, and Chemistry aircraft campaign (SOUTHTRAC) in the 2019 austral winter. These data are analyzed and correlated with quantities characterizing the ambient airflow and the magnitudes of vertical energy propagation through internal gravity waves. The observed turbulence events are strongly correlated with elevated shear values, and overturning gravity waves do not appear to play a role. A highlight of the analysis is the validation of a recently implemented Clear Air Turbulence (CAT) forecast index in the European Centre for Medium‐Range Weather Forecast integrated forecast system. Here we find a slightly better correlation of the CAT prediction with the HALO research aircraft observations compared to those of commercial aircraft. The observed turbulence during SOUTHTRAC was never stronger than moderate, as EDR values remained below 0.3 m 2/3  s −1 . In general, light and light‐to‐moderate turbulence events were extremely rare, occurring in only about 5% of the flight time, and stronger events in less than 0.2%. These results are also reflected in the local atmospheric conditions, which were dominated by a thermally very stable airflow with low vertical shear and large Richardson numbers. Plain Language Summary: This study analyzes high‐resolution data of velocity components in the upper troposphere and lower stratosphere collected with the German research aircraft High Altitude and Long Range Research Aircraft during the Southern Hemisphere Transport, Dynamics, and Chemistry (SOUTHTRAC) campaign in September–November 2019. Flights were conducted predominantly over the southern part of South America, the Drake Passage, and the Antarctic Peninsula. The objective of the analysis was to determine the eddy dissipation rates during the 22 flights. The cubic root of eddy dissipation rates is a common measure used to characterize turbulent regions in the atmosphere. High quality observations with a very accurately calibrated sensor are rare, especially in the remote areas of the SOUTHTRAC campaign. Observed eddy dissipation rates have been correlated with gravity wave activity, but these correlations are very small. A much stronger dependence of the eddy dissipation rates exists on the vertical shear of the horizontal wind. Thus, mechanical generation of turbulence appears to dominate in the observed cases. Overall, the observed turbulence was never stronger than moderate. Turbulence events were extremely rare, occurring in only about 5% of the flight time, and stronger events less than 0.2%. Finally, the observed eddy dissipation rates were compared with weather model forecasts, demonstrating their reliability in predicting turbulent regions. Key Points: Small eddy dissipation rates were observed in the free atmosphere along extended research flights during Southern Hemisphere Transport, Dynamics, and Chemistry in austral winter 2019 Stronger turbulence events are rare and are mostly correlated with enhanced vertical shear of the horizontal wind EDR predictions of a 15‐member ensemble shows higher correlation with research aircraft observations than with those by commercial aircraft